Genomic Insights into Plant Growth-Promoting Traits of Lysinibacillus fusiformis and Bacillus cereus from Rice Fields in Panama - Celestino Aguilar; Rito Herrera; José L. Causadías; Betzaida Bernal; Oris Chavarria; Claudia González; Jessica Gondola; Ambar Moreno; Alexander A. Martínez (Microbiology Research)
Soil, rhizosphere, and plant-associated microorganisms can enhance plant growth and health. A genomic analysis of these microbes revealed the key characteristics contributing to their beneficial effects. Following a field survey in Panama, four bacterial isolates with plant growth-promoting traits (PGPT) in rice (Oryza sativa L.) were identified. In this study, we sequenced, assembled, and annotated the genomes of Lysinibacillus fusiformis C6 and 24, and Bacillus cereus D23 and 59. The C6 genome was 4,754,472 bp long with 10 contigs, 37.62% guanine-cytosine (GC) content, and 4657 coding sequences (CDS). The 24 genome was 4,683,219 bp with five contigs, 37.65% GC content, and 4550 CDS. The D23 genome was 6,199,908 bp long with 18 contigs, 34.84% GC content, and 6141 CDS. The 59 genome was 6,194,462 bp with 21 contigs, 34.87% GC content, and 6122 CDS. Digital DNA–DNA hybridization (dDDH) and average nucleotide identity (ANI) confirmed that C6 and 24 belong to Lysinibacillus fusiformis, whereas D23 and 59 belong to the Bacillus cereus species. Further results revealed that these bacteria contained genes characteristic of plant growth-promoting bacteria, such as siderophore, phytohormone auxin (IAA) production, and nitrogen-fixing abilities that promote plant growth. Moreover, the antiSMASH database identified gene clusters involved in secondary metabolite production (biosynthetic gene clusters), such as betalactone, NRPS-like, NRP-siderophore, terpene, and RiPP-like clusters. Moreover, diverse and novel biosynthetic clusters (BCGs) have included non-ribosomal peptides (NRPs), polyketides (PKs), bacteriocins, and ribosomally synthesized and post-transcriptionally modified peptides (RiPPs). This work offers new insights into the genomic basis of the studied strains’ plant growth-promoting capabilities.